Peningkatan Literasi Kader Posyandu tentang Stunting dan Infeksi Tuberculosis dengan Metode Emotional Demonstration (Emo-Demo) - Laudil Machfud Al Aziz; Fatimah Az Zahroh; Tyas Nirmala Sari; Euvia Kusuma Rachmy Affandi; Intan Choirunnisa; Farida Wahyu Ningtyias (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Stunting and Tuberculosis (TB) are still serious health problems in Indonesia, due to the low level of public knowledge about stunting and TB, so a solution is needed in the form of nutrition education. One of the recommended nutrition education methods is the Emo-Demo method, because this method has a high success rate for increasing awareness and behavior change. This community service aims to increase cadres' knowledge about stunting and tuberculosis (TB) using the Emo-Demo method. This community service was carried out at Posyandu Anyelir 47 Klungkung Village, Sukorambi District, Jember Regency on May 23, 2024. The targets of this community service are cadres totaling 10 people. The results of increasing cadre knowledge in this community service activity were analyzed by the Wilcoxon non-parametric test to measure the difference in the mean values of two paired samples. In the cadre Pre-test results, the average value was 60% and during the Post-test the cadre's knowledge increased to 80%. The Wilcoxon Pre-test and Post-test test results obtained a value of 0.046 <0.05, meaning that there is an average difference between the level of knowledge about stunting and tuberculosis after education with the Emo-Demo method. Based on this, it can be concluded that there is an increase in knowledge of cadre about stunting and TB infection after nutrition education with the Emo-Demo method, and this method can be used for knowledge improvement activities in the community.